Keunggulan dan Penciri Utama Calon Varietas Kangkung RKS 06 pada Dataran Rendah - Ardi Wijayago; Rajiman Rajiman; Elea Nur Aziza (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2023)
The purpose of this study was to identify the benefits and primary features of the proposed RKS 06 kangkong variety. The study was carried out in January through May 2023 at the Karangsari experimental field of Polytechnic for Agricultural Development in Yogyakarta Magelang, Sleman Regency, Yogyakarta Special Region. The experimental design was Complete Randomized Block Design (RAKL) with four replications using The RKS 06, Pusaka 33, KNBI001, and KD 99 variety as factors. Qualitative characters such as stem cross-sectional shape, stem color, leaf shape, leaf color, flower form, petal color, flower crown color, and head color were tested. Kangkong flavor, seed color, seed form, and pistil, harvest age, plant height, stem diameter, leaf length, leaf breadth, number of seeds per capsule, weight per plant, kangkong storageability, weight of 1000 seeds, yield per hectare, and seed demand per hectare were tested quantitative features Utilizing analysis of variance (ANOVA) and the 5% BNJ test, observational data were examined. The results demonstrated that the proposed RKS 06 kangkong variety had high production per hectare (21.8 tons/hectare). The primary features of proposed RKS 06 kangkong variety were the shape of elongated spear-shaped leaves with a tapering tip and a dark green stem color (RHS 144B).